Semantic Structure of the Indonesian ‘Die’ Verbs - Wardani, Yohana Ari (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2023)
This article focuses on the analysis of the semantic structure of the Indonesian ‘die’ verbs. The lexicon variations for the Indonesian ‘die‘ verbs depend on to whom and in what way it is perceived when it happens. The Indonesian ‘die’ verbs have their meaning which can be expressed through the study of the Natural Semantic Metalanguage (NSM) theoretical framework developed by Goddard and Wierzbicka (2013). The method used is a descriptive method with a qualitative research form. The data analysis technique used four steps including determining the semantic prime, looking for the derivation of meaning, determining polysemy based on the object, and paraphrasing meaning. To analyze the meaning of ‘die’ in Indonesian, the data used in this article were collected from the entry word 'mati' obtained from the dictionary https://kbbi.kemdikbud.go.id/entri/mati. The results showed that there were 17 lexicons (meninggal dunia, tutup usia, wafat, berpulang, gugur, mangkat, berlalu, berkalang tanah, berputih tulang, dipanggil Tuhan, mati, mampus, tewas, binasa, koit, modar, and jangkang) reffering to the ‘die’ concept, which were then grouped into two categories based on the entity and the result of which the ‘die’ concept was implemented.